Light and shadows illuminating the women behind the camera - Gonzalvo, Pauline Joyce M. (2013)
"This research is about the women behind the camera - who they are, what they are doing, where are they working, and how they are faring in a male-dominated profession. It also formulates an explanation for the absence of female camera operators in the mainstream television networks, both in the production of news and entertainment programs. The media industries and the audiences have become so used to the concept and image of the cameraman that few people ever ask why there is hardly any woman who holds the camera. Not a nuisance of language alone, it is an indicator of a greater social imbalance rooted in the dynamics of technology, gender and power relations. Guided by Pierre Bourdieu's theory of habitues and male domination, Judy Wajcman's technofeminist theory, and concepts about Filipino culture, I present an analysis of qualitative interviews with nine Filipino cinematographers and the heads of camera operations in ABS-CBN's news and current affairs and entertainment departments. The data is arranged into the following themes: (1) assumptions and misconceptions on females and camera operations, (2) factors that allowed some women to succeed in the field of cinematography, and (3) reasons for the absence of female camera operations in mainstream television networks. My personal narrative as an aspiring videographer and camera operator is integrated into the study, side by side with the data gathered through the interviews. Ultimately, this research is an attempt to level the playing field by challenging society's pre-conceived notion that only men can handle and operate the camera."